Expert Witness and the Court System - A. O, Enofe (2015)
The objective of this study was to examine the role of a forensic accountant as an expert witness in the law court in Nigeria. The study focused on the extent an expert’s professional experience can assist a lawyer in a case, the expert’s assistance in determining the appropriate proximate cause for damages and bases for determining the authenticity of the expert witness’ report. The study adopted an empirical approach using the questionnaire as its instrument in collecting data. These questionnaires were distributed to forensic accountants, accountants and forensic accounting students. The primary data was the main source of data collection, and the simple random sampling method was adopted. The chi-square method was used to analyze the questionnaires. The paper concluded that an expert witness’ professional experience cannot assist a lawyer in a case, because cases differ in nature. The study also revealed that an expert witness has the ability to determine the appropriate proximate cause for damages and the authenticity of an expert’s report can be determined. The study therefore recommended that experts should be assessed on the type and nature of previous professional experiences in relation to the nature of the current case at hand. Key word; Expert witness, court system and litigation support